Comparative study of two dimensional boundary layer over NACA 23012 and NACA 23021 airfoils by using keller’s box method - Kumar, Vinod Kumar K Sivak; Abdullah, Aslam; Basuno, Bambang (Penerbit UTHM, 2022)
This paper begins with general description on various methods for solving boundary layer equation. In particular, Prandtl's boundary layer equation is a simplified version of Navier-Stokes equation that is solved integrally. Order of magnitude analysis can be used to solve laminar and turbulent flow problems along the boundary layer. A more complex technique based on Keller’s box method is also discussed. This study aims at utilising a developed computer code which allows one to predict the development of boundary layer characteristics along airfoils’ surface, and have a comparative understanding on flow behaviours between NACA 23012 and NACA 23021 airfoils, as well as 0⁰ and 5⁰ angles of attack. The ability of Keller’s box method to solve the boundary layer equation prevails through correct skin friction, momentum thickness, and shape factor distributions over the surfaces. It was found that skin friction in boundary layer over NACA 23021 is higher than that over NACA 23012 for about 10% of the chord length from the leading edge. However, momentum thickness of the boundary layer over NACA 23021 is less than the boundary layer momentum thickness over NACA 23012 for the whole chord length. Similarly, the shape factor H for the boundary layer over the former is smaller in comparison to the latter for about 30% of the chord length.